Fast heating with a PW laser as a step to ignition - Kodama, R; Azechi, H; Fujita, H; Habara, H; Izawa, Y; Jitsuno, T; Jozaki, T; Kitagawa, Y; Krushelnick, K; Matsuoka, T; Mima, K; Miyanaga, N; et al. (2004)
We have developed PW(0.5ps/500J) laser system to demonstrate fast heating of imploded core plasmas using a hollow cone shell target. Significant enhancement of thermal neutron yield has been realized with PW-laser heating, confirming that the high heating efficiency is maintained as the short-pulse laser power is substantially increased to near equivalent power to the ignition condition. The efficient heating could be caused by the efficient guiding of heating pulse with the hollow cone and self-organized relativistic electron transport. According to the experimental results, we are now developing a 10kJ-PW laser system to study the ignition-equivalent temperature heating physics.